Proses Editing Video Podcast Menggunakan Perangkat Lunak Adobe Premiere Pro untuk Meningkatkan Konten Digital di Kanal YouTube Ampu Studio - Khanif Haryadi; Dhanar Intan Surya Saputra (Pusat Riset dan Inovasi Nasional, 2026)
The development of digital content on the YouTube platform encourages creators to produce more engaging and informative podcast videos through the editing process. This study discusses the video podcast editing workflow of the Tikitalk program on the Ampu Studio YouTube channel using Adobe Premiere Pro. This research also aims to understand how the editing stages are carried out in improving the quality of video podcast presentation. The research method used is descriptive qualitative through direct observation during internship activities, so that the data is obtained based on real field experience. The results of the study show that the editing process, such as video cutting, transition settings, audio adjustment, audio censoring, and the addition of motion graphics, can significantly improve the quality of video podcast presentation. In addition, this process also helps make the content more organized, informative, and engaging for viewers. Thus, the role of the editor in the production process is very important in supporting the quality of digital content on the YouTube platform. Therefore, it can be concluded that editing is not only a technical process, but also an important part in increasing the attractiveness and professionalism of a video podcast.